JEJAK-JEJAK PERADABAN KUNO DI DESA GETASAN - I Nyoman Sunarya (Balai Arkeologi Bali, 2015)
Indication that ancient civilization has ever developed here is supported by archaeological remains found in Getasan Village. This research aims to understand the development of Getasan civilization in order to provide the information needed to reconstruct the cultural history of Bali. Data were collected through observation, i.e. excavation and survey, interview, and literature study. Data analysis was done through identification of archaeological remains, associated with the concepts of civilization. The results of analysis were presented using descriptive-qualitative approach. The result of this research shows that the findings of the structure in Getasan Village indicates the development of ancient civilization. The trails of civilization which were found there was a continuity from the previous culture. The interpretation is supported with the findings from survey that covers several locations in Getasan Village.Indikasi bahwa di Desa Getasan pernah berkembang peradaban masa lalu didukung juga dengan tinggalan-tinggalan arkeologinya. Penelitian ini bertujuan untuk mengetahui perkembangan peradaban di Desa Getasan agar mampu melengkapi informasi dalam merekonstruksi sejarah kebudayaan Bali. Pengumpulan data dilakukan melalui observasi, meliputi ekskavasi dan survei, wawancara, serta studi kepustakaan. Analisis dilakukan melalui identifikasi tinggalan arkeologi yang dikaitkan dengan konsep-konsep peradaban. Hasil analisis kemudian disajikan secara deskriptif-kualitatif. Hasil penelitian menunjukkan bahwa temuan struktur di Desa Getasan mengindikasikan pernah berkembangnya peradaban kuno di wilayah ini. Desa Getasan memiliki jejak-jejak peradaban yang merupakan kelanjutan dari kebudayaan sebelumnya. Penafsiran tersebut didukung dengan temuan-temuan hasil survei yang dilakukan di beberapa lokasi di wilayah Desa Getasan.